The Beginning of the Uzbek Farming Movement: Initial Stages, Problems, and Characteristics - Intizom, Khujamatov (American Journal of Biodiversity, 2025)
The article discusses the development of farms and their activities in the agricultural sector in Uzbekistan during the period of independence.